Dosmestikasi Ikan Gabus, Channa Striata Blkr, Upaya Optimalisasi Perairan Rawa di Provinsi Kalimantan Selatan - Untung Bijaksana (Jurnal Lahan Suboptimal : Journal of Suboptimal Lands, 2012)
Bijaksana, U. 2012. Snakehead Domestication, Channa Striata Blkr, Swamp Water Optimization Efforts in South Kalimantan Province. J. Lahan Suboptimal 1(1):92-101.This research aimed at domesticating snakehead in order to fulfill the consumption without relying on catch. This research was conducted in the Wet Laboratory of the Department of Aquaculture Faculty of Fisheries Banjarbaru from September to October 2006. Snakeheads caught in "beje 'were selected according to weight and size and then kept in concrete tanks. A total of 32 pairs were placed in the experimental tanks.Feed was served as much as 4% of bodyweight/day for 4 times/day. Observations were made at the beginning and end of the experiment which included concentration of E2, egg diameter, IGS, IHS and fecundity. The results obtained were as the followings: water enhancement was associated with the development of the IGS with r2 = 0.92 which was greater than that of the decrease in water with r2=0.55.Greater reduction in water was associated with IHS with r2=0.96 which was greater then that of raising the water with r2 only 0.74. Increase of water associated with the concentration of estradiol-17 beta with r2=0.82 was greater than that of the decrease of water which was was only 0.55.The decline and rise of water were aasociated with the diameter of each egg with the r2=0.93 and 0.96. Enhancement of water associated with agreater effect on fecundity with the r2=0.74 while decreasing water with the r2=0.36. Several indicators of snakehead reproduction obtained from the experiment were found to be similar with those naturally occured. It was concluded that the snakehead’s gonad could be grown to reach maturity level in the container as a domestication process.